Biogeochemical markers in juvenile Leach's storm-petrels (Hydrobates leucorhous) stranded offshore are distinct from inshore stranded juveniles and nestlings - Anne N.M.A. Ausems; Sophie Roy; Alexander L. Bond; Laura Crick; Joshua T. Cunningham; April Hedd; Laura A. McFarlane Tranquilla; Jennifer C. Rock; Robert A. Ronconi; Katharine R. Studholme; Christopher R.E. Ward; Sabina I. Wilhelm; et al. (Marine Pollution Bulletin, 2026)

Bioaccumulation of trace elements by Leach's storm-petrels (Hydrobates leucorhous) in the North and South Atlantic Ocean during the non-breeding period - Catherine Potvin; Manon Sorais; Robert A. Ronconi; Katharine R. Studholme; April Hedd; Alexander L. Bond; Vegard S. Bråthen; Sydney M. Collins; Laura Crick; Joshua T. Cunningham; Anne N.M.A. Ausems; David A. Fifield; et al. (Marine Pollution Bulletin, 2026)

Bovine milk glycoproteins concentration influences bacterial growth and anti-pathogenic bioactivities relevant to the infant gut in vitro - Iwona Dziembała-Gładysz; Marie Le Berre; Stephen Cunningham; Laura Walsh; Uthesh Umapathy; Yousef Joubran; Gerard T.A. Fleming; David A. Goulding; Lokesh Joshi; Jonathan O'Regan; Michelle Kilcoyne (International Dairy Journal, 2026)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Navigating the risks and rewards of scavenging in multipredator, human‐impacted landscapes - Calum X. Cunningham; Rebecca Windell; Lauren C. Satterfield; Aaron J. Wirsing; Thomas M. Newsome; Taylor R. Ganz; Laura R. Prugh (Ecology, 2025)
Large carnivores can influence smaller scavengers through both positive and negative interactions (e.g., carrion provisioning and intraguild killing) and ultimately shape scavenging efficiency. However, we know little about this trade‐off in anthropogenic landscapes where humans kill carnivores and provide carrion subsidies. In the context of wolf ( Canis lupus ) recolonization of human‐impacted landscapes in Washington, USA, we investigated how sources of ungulate mortality (wolves, cougars [ Puma concolor ], and vehicles) shape scavenging efficiency, community‐wide carcass visitations, and the strategies used by scavengers to navigate risk–reward trade‐offs. Cougar and wolf kills mostly occurred in areas with low‐to‐moderate human influence, whereas roadkill typically occurred in areas with high human impact. Wolves consumed their kills most rapidly (median Cathartes aura ) and black bears ( Ursus americanus ), which are obligate and apex scavengers, respectively, coincided with a seasonal increase in scavenging by most other species. The two mammalian mesocarnivores exhibited divergent strategies: Coyotes ( Canis latrans ) frequently scavenged but usually for short durations and with heightened vigilance at predator kills, whereas bobcats ( Lynx rufus ) visited carcasses less frequently but fed for longer durations and displayed low vigilance while scavenging. These results suggest a hierarchical decision‐making process whereby scavengers first choose whether to forage at a carcass before fine‐tuning foraging duration, using temporal refugia, or increasing vigilance. Predator recovery in human‐dominated landscapes therefore adds complexity to the spatiotemporal landscape of risks and rewards, and outcomes for scavengers will likely depend on their propensity to scavenge and vulnerability to humans and large predators.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Under pressure: inhibited sporophyte growth of the sugar kelp Saccharina latissima (Phaeophyceae) - Eoghan Mánus Cunningham; Luka Seamus Wright; Molly Crowe; Emma Healey; Laura F. Robinson; Hong Chin Ng; Louise Kregting (Journal of Applied Phycology, 2024)
Seaweed aquaculture, which takes place mostly in Asia, is a lucrative industry that is valued > US $9 billion. However, technological modifications are needed to ensure economic viability and growth of the seaweed aquaculture industry throughout Europe. While current research is investigating the use of certain mechanised processes in seaweed aquaculture, the impact of pressurised spraying of macroalgal cultures on subsequent growth remains unknown. Here, we aimed to determine the efficacy of a future mechanised seeding procedure by investigating how differing pressure treatments impact upon the growth and percentage cover of zoospores seeded onto twine in the hatchery, using the kelp Saccharina latissima as a model species. Zoospore solutions were subjected to pressures of 1, 2, 3, 4, and 5 bar, before being seeded on hatchery twine and left to grow for 7 weeks. We demonstrate that both percentage cover and sporophyte lengths for S. latissima are significantly reduced by ~ 22% and ~ 61%, respectively, when juvenile zoospores are subjected to increasing pressure from 1 to 5 bar. This indicates that minimal pressure in the use of mechanised hatchery techniques is optimal for growth of seaweed.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Climate-Relevant Ocean Transport Measurements in the Atlantic and Arctic Oceans - Barbara Berx; Denis Volkov; Johanna Baehr; Molly Baringer; Peter Brandt; Kristin Burmeister; Stuart Cunningham; Marieke de Jong; Laura de Steur; Shenfu Dong; Eleanor Frajka-Williams; Gustavo Goni; et al. (Oceanography, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Arctic Mediterranean exchanges: a consistent volume budget and trends in transports from two decades of observations - Svein Østerhus; Rebecca Woodgate; Héðinn Valdimarsson; Bill Turrell; Laura de Steur; Detlef Quadfasel; Steffen M. Olsen; Martin Moritz; Craig M. Lee; Karin Margretha H. Larsen; Steingrímur Jónsson; Clare Johnson; et al. (Ocean Science, 2019)
The Arctic Mediterranean (AM) is the collective name for the Arctic Ocean, the Nordic Seas, and their adjacent shelf seas. Water enters into this region through the Bering Strait (Pacific inflow) and through the passages across the Greenland–Scotland Ridge (Atlantic inflow) and is modified within the AM. The modified waters leave the AM in several flow branches which are grouped into two different categories: (1) overflow of dense water through the deep passages across the Greenland–Scotland Ridge, and (2) outflow of light water – here termed surface outflow – on both sides of Greenland. These exchanges transport heat and salt into and out of the AM and are important for conditions in the AM. They are also part of the global ocean circulation and climate system. Attempts to quantify the transports by various methods have been made for many years, but only recently the observational coverage has become sufficiently complete to allow an integrated assessment of the AM exchanges based solely on observations. In this study, we focus on the transport of water and have collected data on volume transport for as many AM-exchange branches as possible between 1993 and 2015. The total AM import (oceanic inflows plus freshwater) is found to be 9.1 Sv (sverdrup, 1 Sv =106 m3 s−1) with an estimated uncertainty of 0.7 Sv and has the amplitude of the seasonal variation close to 1 Sv and maximum import in October. Roughly one-third of the imported water leaves the AM as surface outflow with the remaining two-thirds leaving as overflow. The overflow water is mainly produced from modified Atlantic inflow and around 70 % of the total Atlantic inflow is converted into overflow, indicating a strong coupling between these two exchanges. The surface outflow is fed from the Pacific inflow and freshwater (runoff and precipitation), but is still approximately two-thirds of modified Atlantic water. For the inflow branches and the two main overflow branches (Denmark Strait and Faroe Bank Channel), systematic monitoring of volume transport has been established since the mid-1990s, and this enables us to estimate trends for the AM exchanges as a whole. At the 95 % confidence level, only the inflow of Pacific water through the Bering Strait showed a statistically significant trend, which was positive. Both the total AM inflow and the combined transport of the two main overflow branches also showed trends consistent with strengthening, but they were not statistically significant. They do suggest, however, that any significant weakening of these flows during the last two decades is unlikely and the overall message is that the AM exchanges remained remarkably stable in the period from the mid-1990s to the mid-2010s. The overflows are the densest source water for the deep limb of the North Atlantic part of the meridional overturning circulation (AMOC), and this conclusion argues that the reported weakening of the AMOC was not due to overflow weakening or reduced overturning in the AM. Although the combined data set has made it possible to establish a consistent budget for the AM exchanges, the observational coverage for some of the branches is limited, which introduces considerable uncertainty. This lack of coverage is especially extreme for the surface outflow through the Denmark Strait, the overflow across the Iceland–Faroe Ridge, and the inflow over the Scottish shelf. We recommend that more effort is put into observing these flows as well as maintaining the monitoring systems established for the other exchange branches.

The accessibility and utilization of genetic testing for inherited heart rhythm disorders: a Canadian cross-sectional survey study - Thomas M. Roston; Laura Dewar; Sonia Franciosi; Julie Hathaway; Kirsten Bartels; Taylor Cunningham; Karen A. Gibbs; Sam Sheps; Zachary W. M. Laksman; Shubhayan Sanatani; Andrew D. Krahn (Journal of Community Genetics, 2018)

Naloxone effects on extinction of ethanol- and cocaine-induced conditioned place preference in mice - Laura Font; Christa A. Houck; Christopher L. Cunningham (Psychopharmacology, 2017)

Development of a Theory-based, Sociocultural Instrument to Assess Black Maternal Intentions to Vaccinate Their Daughters Aged 9 to 12 Against HPV - Jennifer Cunningham-Erves; Laura L. Talbott; Marcia R. O’Neal; Nataliya V. Ivankova; Kenneth A. Wallston (Journal of Cancer Education, 2016)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

3rd Annual Conference of the Leverhulme Centre for Integrative Research on Agriculture and Health (LCIRAH), Developing methods in agriculture and health research, London, 13–14 June 2013 - Jody Harris; Mieghan Bruce; Elisa Cavatorta; Laura Cornelsen; Barbara Häsler; Rosie Green; Emily H. Morgan; Sara Stevano; Helen L. Walls; Kenda Cunningham (Food Security, 2013)

A millennial long March–July precipitation reconstruction for southern-central England - Rob Wilson; Dan Miles; Neil J. Loader; Tom Melvin; Laura Cunningham; Richard Cooper; Keith Briffa (Climate Dynamics, 2013)

Paleoecological evidence of major declines in total organic carbon concentrations since the nineteenth century in four nemoboreal lakes - Laura Cunningham; Kevin Bishop; Eva Mettävainio; Peter Rosén (Journal of Paleolimnology, 2011)

Fourier transform infrared spectroscopy, a new method for rapid determination of total organic and inorganic carbon and biogenic silica concentration in lake sediments - Peter Rosén; Hendrik Vogel; Laura Cunningham; Nina Reuss; Daniel J. Conley; Per Persson (Journal of Paleolimnology, 2010)

Effects of climate on organic carbon and the ratio of planktonic to benthic primary producers in a subarctic lake during the past 45 years - Peter Rosén; Laura Cunningham; Jorien Vonk; Jan Karlssona (Limnology and Oceanography, 2009)
The effects of climatic variables on lake‐water total organic carbon (TOC) concentrations and benthic and pelagic primary producers during the past 45 yr were assessed using the sediment records of two subarctic lakes, one with mires and one without mires connected to the lake. The lake with a mire showed large and synchronous changes in the planktonic to benthic (P : B) ratio of diatoms and concentrations of TOC inferred from nearinfrared spectroscopy. During periods of warm temperatures, high precipitation, and long ice‐free conditions, we inferred high TOC in the lake, and the diatom community was dominated by planktonic species. The stable carbon isotopic (Δ 13 C) values of sediment organic matter were negatively correlated with inferred TOC concentration and P :B ratio. We suggest that the changes in TOC and P : B ratio were a result of changing climate, permafrost degradation, and related changes in the catchment. Terrestrial organic matter, by its strong effect on the penetration of light through the lake water, possibly affected the habitats available for benthic photosynthesis and thus the Δ13C of the sediment organic matter. The large changes in recent times may also be because of unusually long ice‐free periods, warmer temperatures, and other associated limnological changes. The lake with no mire next to the lake showed only minor changes in lake‐water TOC during the same period and P :B ratio remained almost constant until the past 5 yr, when the P :B ratio increased rapidly. The observed changes in P :B ratio within this lake may be because of complex interactions of several climate‐related variables.

Reference-dose place conditioning with ethanol in mice: empirical and theoretical analysis - Peter A. Groblewski; Laura S. Bax; Christopher L. Cunningham (Psychopharmacology, 2008)

Predicting Pathogen Introduction: West Nile Virus Spread to Galápagos - A. MARM KILPATRICK; PETER DASZAK; SIMON J. GOODMAN; HELMUTH ROGG; LAURA D. KRAMER; VIRNA CEDEÑO; ANDREW A. CUNNINGHAM (Conservation Biology, 2006)
Emerging infectious diseases are a key threat to conservation and public health, yet predicting and preventing their emergence is notoriously difficult. We devised a predictive model for the introduction of a zoonotic vector‐borne pathogen by considering each of the pathways by which it may be introduced to a new area and comparing the relative risk of each pathway. This framework is an adaptation of pest introduction models and estimates the number of infectious individuals arriving in a location and the duration of their infectivity. We used it to determine the most likely route for the introduction of West Nile virus to Galápagos and measures that can be taken to reduce the risk of introduction. The introduction of this highly pathogenic virus to this unique World Heritage Site could have devastating consequences, similar to those seen following introductions of pathogens into other endemic island faunas. Our model identified the transport of mosquitoes on airplanes as the highest risk for West Nile virus introduction. Pathogen dissemination through avian migration and the transportation of day‐old chickens appeared to be less important pathways. Infected humans and mosquitoes transported in sea containers, in tires, or by wind all represented much lower risk. Our risk‐assessment framework has broad applicability to other pathogens and other regions and depends only on the availability of data on the transport of goods and animals and the epidemiology of the pathogen.

Benthic diatom communities as indicators of anthropogenic metal contamination at Casey Station, Antarctica - Laura Cunningham; Ben Raymond; Ian Snape; Martin J. Riddle (Journal of Paleolimnology, 2005)

Distal and proximal pre-exposure to ethanol in the place conditioning task: tolerance to aversive effect, sensitization to activating effect, but no change in rewarding effect - Christopher L. Cunningham; Laura E. Tull; Kirsten E. Rindal; Paul J. Meyer (Psychopharmacology, 2002)